Radiotherapy for Melanoma: More than DNA Damage. (3rd April 2019) - Rogers, Susanne J.; Puric, Emsad; Eberle, Brigitte; Datta, Niloy R.; Bodis, Stephan B.
Abstract : Despite its reputation as a radioresistant tumour, there is evidence to support a role for radiotherapy in patients with melanoma and we summarise current clinical practice. Melanoma is a highly immunogenic tumour and in this era of immunotherapy, there is renewed interest in the potential of irradiation, not only as an adjuvant and palliative treatment, but also as an immune stimulant. It has long been known that radiation causes not only DNA strand breaks, apoptosis, and necrosis, but also immunogenic modulation and cell death through the induction of dendritic cells, cell adhesion molecules, death receptors, and tumour-associated antigens, effectively transforming the tumour into an individualised vaccine. This immune response can be enhanced by the application of clinical hyperthermia as evidenced by randomised trial data in patients with melanoma. The large fraction sizes used in cranial radiosurgery and stereotactic body radiotherapy are more immunogenic than conventional fractionation, which provides additional radiobiological justification for these techniques in this disease entity. Given the immune priming effect of radiotherapy, there is a strong but complex biological rationale and an increasing body of evidence for synergy in combination with immune checkpoint inhibitors, which are now first-line therapy in patients with recurrent or metastatic melanoma. There is great potential to increase local control and abscopal effects by combining radiotherapy with both immunotherapy and hyperthermia, and a combination of all three modalities is suggested as the next important trial in this refractory disease.